Identifikasi Senyawa Fitokimia dan Aktivitas Antioksidan Minuman Fungsional Cascara dari Kulit Kopi dengan Fermentasi Terkendali - Umi Rosidah; Sugito Sugito; Kiki Yuliati; Abdiansyah Abdiansyah; Fatin Anggraini (Seminar Nasional Lahan Suboptimal, 2021)
Rosidah U, Sugito S, Kiki Yuliati K, Abdiansyah A, Anggraini F. 2021. Identification phytochemical compounds and antioxidant activity of cascara functional drink derived from coffee skin by controlled fermentation. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-9 Tahun 2021, Palembang 20 Oktober 2021. pp. 611-620. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI). The effect of relative humidity of fermentation room on phytochemical compound content and antioxidant activity of coffee skin-derived cascara was determined in this study. Robusta coffee skin was collected from Semendo, Muara Enim district, South Sumatera. A factorial completely randomized design was used and two factors were investigated, namely relative humidity of fermentation room (80, 85, 90 and 95 percent) and serving form of product (powder and solution). All experiment was carried out in triplicates. The observed parameters included both qualitative (saponin, flavonoid, alkaloid, and tannin test) and quantitative (pH value, phenol content, tannin content and antioxidant activity (IC50)) characteristics. The resuls revealed that all samples contained saponin, flavonoid, alkaloid, and tannin, both in powdered and in cascara solution. Relative humidity of fermentation room showed significantly increased pH value, total phenol content, tannin content and increased antioxidant activity. On the other hand, serving form of product showed significantly increased pH value, decreased total phenol content and tannin content.  Furthermore, interaction of the two factors showed significant effects on pH value and total phenol content. In conclusion, powdered cascara fermented in 95 per cent relative humidity was the best treatment, since it contained saponin, flavonoid, alkaloid, and tannin and hat pH of 5.84, total phenol content of 2.45 mg/g, tannin content of 3.67 mg/g and IC50 of  67,94 mg/kg.